Reframing Arabic Reading Instruction: The Role of Digital Comics in Fostering Deeper Textual Understanding - Ahmad Fauzi; Nisa Ulfi Jannah; Shofil Fikri (https://unikhams.ac.id/, 2025)
Background of study: Many learners still encounter challenges in reading Arabic texts, often caused by limited vocabulary, low engagement, and instructional strategies that fail to connect with students' context and interests. Aims and scope of paper: This research seeks to examine how digital comics can function as an alternative learning medium to support the development of maharah qirā’ah by integrating visual narratives with textual elements. Methods: Using a qualitative descriptive design, the study relies on literature-based data and content analysis of Arabic-themed digital comics. Sources include previous studies, theoretical frameworks, and instructional media evaluations. Result: The findings suggest that digital comics contribute positively to student motivation and comprehension. The visual-verbal combination not only helps learners grasp meaning more effectively but also stimulates emotional and cognitive engagement. The comics’ narrative structure also supports moral and cultural literacy in a familiar, student-centered format. Conclusion: Integrating digital comics into Arabic reading lessons provides both pedagogical and affective benefits. Their alignment with multimedia learning theory highlights their potential to enhance not just understanding, but also the overall reading experience in a more dynamic and relevant way.